Penggunaan Mind Map Untuk Materi Asam Basa Kelas Xi Sma/Ma - Anisa Aurum Ningtyas (Publikasi Indonesia, 2022)
This research is a development that aims to develop a chemistry mind map enrichment book acid and base solution material and to know the quality of the chemistry mind map enrichment book. This research uses an ADDIE (Analysis, Design, Development or Production, Implementation or Delivery and Evaluations) development model. The data obtained in the form of data product development process based on expert advice and input from the media, materials experts, peer reviewer, learners, and reviewers, as well as data quality level of products based on an assessment of five reviewers. Assessment instrument consisting of 24 items indicators. Results of the assessment in the form of quantitative data in the form of a score, then converted into qualitative data quality enrichment books chemistry mind map, based on the assessment criteria ideal. Aspects assessed include feasibility aspects of content, presentation, and a mind map. The results obtained are already successfully compiled book mapmateri mind enrichment solution chemistry of acids and bases with the percentage of each aspect ideals are respectively 91.5%, 88.57%, and 87.56%, so it was concluded that the chemistry mind map enrichment book acid and base solution material has a very good quality (SB) for these three aspects and fit for use as a textbook for students learning.